Eastern Platinum Limited: Operations Resume at Crocodile River Mine-Two Year Wage Agreement Reached With NUM (Marketwire, 2011)
(Marketwire - May 24, 2011) - Eastern Platinum Limited ("Eastplats" or the "Company") (TSX:ELR)(AIM:ELR)(JSE:EPS) is pleased to report that as of Friday 20th May, full mining operations have resumed at the Crocodile River Mine ("CRM"), and a two year wage agreement has been reached with the National Union of Mineworkers ("NUM"). Management at CRM have continued to constructively engage with NUM and confirmed that all employees at the mine, except the 155 who are subject to disciplinary action, have returned to work as of Friday 20th May. Following extensive negotiations with NUM, a two-year wage agreement has been reached with NUM which provides for an effective cost to company increase of approximately 10% year-on-year commencing March 1, 2011. The Company is very pleased to have reached an agreement on wages, benefits and other production related issues and recognizes the efforts of both CRM management and NUM leadership on the outcome achieved.